Sailing a beginner's manual - Driscoll, John (Fernhurst, 1987)
Sailing will give you an interest for life. The scope is endless: pottering, cruising and racing; dinghies, keelboats and yachts; rivers, lakes and the sea. Few activities offer so much fun and so much variety.